2016
DOI: 10.1080/10245332.2016.1150410
|View full text |Cite
|
Sign up to set email alerts
|

The level of peripheral blood circulating CD34+ cells is higher in acute promyelocytic leukemia patients with adverse prognostic factors

Abstract: The circulating CD34+ cell count appears to increase in some APL patients and a higher CD34+ cell count may be indicative of inferior survival and serve as an adverse biomarker for APL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Evaluation of the full text was performed for 242 studies, of which 218 were excluded given the lack of outcome or mutations of interest. Finally, a total of 24 articles were included in this systematic review [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36], as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the full text was performed for 242 studies, of which 218 were excluded given the lack of outcome or mutations of interest. Finally, a total of 24 articles were included in this systematic review [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36], as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%